A Revolutionary Promise of Justice: Diane Arbus' Self-Portrait, Pregnant, 1945, NYC. Issue 1 (1st August 2017) - Liss, Andrea
A Revolutionary Promise of Justice: Diane Arbus' Self-Portrait Pregnant, 1945 abstract Andrea Liss. My critical musings on this little-known maternal self-portrait are meant to reconceive its meaning as an uncanny predecessor to contemporary feminist embodied knowledge. This knowledge holds the potential for articulating new strategies of respect for the maternal and for the real mother, in other words for thinking m(o)therwise. This portent photograph not only presented a non-normative concept of pregnancy during its cultural moment; it continues to challenge the deep patriarchal "embarrassment" that pregnancy carries. Arbus' performance of the maternal was crafted within her creative practice and deeply embedded within a new maternal structure of projected work and self. Picturing herself as artist/photographer, other, lover and projected mother, she embodies a creative interplay between the passion of theory and the thinking body. This photograph can be viewed at https://onlineonly.christies.com/s/photographs-diane-arbus/self-portrait-pregnant-n-y-c-1945-1/222 .